MATHEMATICS LEARNING STRATEGIES THAT SUPPORT PANCASILA MORAL EDUCATION: PRACTICAL APPROACHES FOR TEACHERS - Harefa, Darmawan; Fatolosa Hulu; Welli Siswanti (Universitas Nias Raya, 2024)
This study aims to identify and develop mathematics learning strategies that support moral education based on the values of Pancasila. Using a qualitative approach, the research involves mathematics teachers from several elementary and secondary schools to explore effective methods for integrating Pancasila values into mathematics instruction. The findings indicate that learning strategies, including contextual learning, collaborative projects, and reflective discussions, can enhance students' understanding of mathematical concepts while also strengthening their character. Additionally, the study identifies challenges in implementing these strategies, including time constraints and a lack of training for teachers. It is hoped that these findings can serve as a reference for developing more effective educational practices in integrating moral values into mathematics learning.